Social Forces That Influence Curriculum - Abdillah, Abdillah; Musleh Wahid (Penerbit Hellow Pustaka, 2025)
The curriculum is an educational instrument that not only reflects educational goals, but is also influenced by social forces in a society. This study aims to analyze the social forces that influence curriculum formulation, especially in Indonesia. Using a qualitative approach, this study explores factors such as politics, economics, and social change as the main elements that play a role in the process of curriculum formulation and implementation. The results of the study indicate that political forces play an important role in determining the direction of the curriculum, especially in responding to government policies related to education. On the other hand, economic factors cannot be ignored, where the needs of the labor market also direct the content and focus of the curriculum. The influence of social movements is also reflected in the development of a curriculum that is more inclusive and responsive to community issues, such as gender equality and social justice.